Impak Online Learning Terhadap Performa Akademik Mahasiswa Akuntansi dengan Worklife Balance Sebagai Variabel Intervening - Haura Dhiya Addina Hamdani; R Rosiyana Dewi (PT. Cendekia Sapta Indonesia, 2022)
This study aims to analyze the effect of Online Learning on Accounting Students' Academic Performance. To analyze the effect of Work-Life Balance on Academic Performance of Accounting Students. To analyze the effect of Online Learning on Work-Life Balance. To analyze the influence of Online Learning on Academic Performance of Accounting Students with Work-Life Balance as an Intervening Variable. The results of this study indicate that online learning has a positive effect on work-life balance, the more effective online learning, the more balanced work-life balance. Online learning has a positive effect on academic performance, the more effective online learning, the higher the academic performance. Work-life balance has a positive effect on academic performance, the more balanced work-life balance on work and online learning systems, the higher the level of academic performance. Online learning positively affects academic performance through Work-Life Balance as an Intervening variable.